2019
DOI: 10.1093/europace/euz289
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular pacing during cardiac magnetic resonance imaging

Abstract: Aims We aimed to assess the effect of cardiac resynchronization on left ventricular (LV) function, volumes, geometry, and mechanics in order to demonstrate reverse remodelling using cardiac magnetic resonance (CMR) with resynchronization on. Methods and results New York Heart Association (NYHA) Class II–III patients on optimal medical therapy with LV ejection fraction (LVEF) ≤35%, and complete LBBB with broad QRS (>150 ms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Beyond conventional CMR parameters, remodelling indices, global strain, global dyssynchrony (i.e., mechanical dispersion, defined as the standard deviation of time to peak longitudinal/circumferential strain in 16 LV segments), and regional dyssynchrony (maximum differences in time between peak septal and lateral transversal displacement), were analysed. The authors found a significant improvement in LV functional and dyssynchrony parameters during biventricular pacing at follow-up [45]. By switching from biventricular to right atrial pacing, an immediate deterioration of LV function and mechanics was observed [45].…”
Section: Assessment Of LV Remodellingmentioning
confidence: 95%
See 3 more Smart Citations
“…Beyond conventional CMR parameters, remodelling indices, global strain, global dyssynchrony (i.e., mechanical dispersion, defined as the standard deviation of time to peak longitudinal/circumferential strain in 16 LV segments), and regional dyssynchrony (maximum differences in time between peak septal and lateral transversal displacement), were analysed. The authors found a significant improvement in LV functional and dyssynchrony parameters during biventricular pacing at follow-up [45]. By switching from biventricular to right atrial pacing, an immediate deterioration of LV function and mechanics was observed [45].…”
Section: Assessment Of LV Remodellingmentioning
confidence: 95%
“…The authors found a significant improvement in LV functional and dyssynchrony parameters during biventricular pacing at follow-up [45]. By switching from biventricular to right atrial pacing, an immediate deterioration of LV function and mechanics was observed [45].…”
Section: Assessment Of LV Remodellingmentioning
confidence: 95%
See 2 more Smart Citations
“…Some recent publications included a limited number of CRT patients within a larger study, 4,5 but most studies to date have included only bipolar LV leads with limited thoracic or chest MRI locations. Exception are the studies of Sheldon et al, 6 who included 1 patient with a quadripolar lead, and Vago et al, 7 who performed cardiac MRI on 13 patients implanted with MRI-conditional CRTs during biventricular pacing (DOO) and right atrial pacing (AOO) with no reported device complications. The use of quadripolar LV leads has become standard of care.…”
Section: Introductionmentioning
confidence: 99%